Forensic Examination of Money and Securities - V. S. Sezonov (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on the peculiarities of forensic examination of money and securities. The purpose of the article is to determine the essence of forensic examination of money and securities.